2019
DOI: 10.1021/acsearthspacechem.8b00212
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Headgroup and Chain Length Dependence of Surface Characteristics of Organic-Coated Sea Spray Aerosols

Abstract: The structure of sea spray aerosols (SSAs) has been described as a saline core coated by organic surfactants. The presence of surface-active compounds at the air-water interface can have a large impact on physical, chemical and optical properties of SSAs. The surfactant molecules chosen for this study, palmitic acid (PA), stearic acid (SA), arachidic acid (AA), methyl palmitate (MP), methyl stearate (MS) and methyl arachidate (MA), were used to investigate the effect of alkyl chain-length, head-groups and sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…Figure shows the reflectance spectra for monolayers deposited from the solid phase region of the isotherm at pH values below and above the AA p K a . We believe that the Cu 2+ is transferred with the monolayer onto the support during the deposition process, based on literature precedent. ,, A reference spectrum for an AA film without metal ions is also shown, with the asymmetric and symmetric −CH 2 stretching bands present at 2918 and 2849 cm –1 , respectively (Figure ), consistent with literature values. ,, The spectra of Cu 2+ -complexed films deposited at low subphase pH values resemble that for the AA layer without Cu 2+ ions (Figure ). In the spectra of monolayers deposited at pH values approaching and surpassing the AA p K a (i.e., pH 5.3, 5.5, and 6.2 in Figure ), band positions were seen to be at slightly lower frequencies: 2915 and 2846 cm –1 for asymmetric and symmetric stretches, respectively (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Figure shows the reflectance spectra for monolayers deposited from the solid phase region of the isotherm at pH values below and above the AA p K a . We believe that the Cu 2+ is transferred with the monolayer onto the support during the deposition process, based on literature precedent. ,, A reference spectrum for an AA film without metal ions is also shown, with the asymmetric and symmetric −CH 2 stretching bands present at 2918 and 2849 cm –1 , respectively (Figure ), consistent with literature values. ,, The spectra of Cu 2+ -complexed films deposited at low subphase pH values resemble that for the AA layer without Cu 2+ ions (Figure ). In the spectra of monolayers deposited at pH values approaching and surpassing the AA p K a (i.e., pH 5.3, 5.5, and 6.2 in Figure ), band positions were seen to be at slightly lower frequencies: 2915 and 2846 cm –1 for asymmetric and symmetric stretches, respectively (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Two important types of surfactant molecules naturally found in the SSML are fatty acids and fatty alcohols. These molecules were recently discovered to exist in a 9:1 ratio in oceanic emission samples . Octadecanoic acid (OA, stearic acid, C 18 OOH), a C 18 saturated fatty acid, is known to be enriched in sea spray aerosol, and octadecanol (OL, stearyl alcohol, C 18 OH) is its C 18 saturated fatty alcohol analogue. , OA is often used as a proxy for the organic film on sea spray aerosol surfaces, because it is the most prevalent oceanic fatty acid along with hexadecanoic acid (palmitic acid, C 16 OOH), both of which are derived from biogenic material including marine organisms. An aim of this study is to emulate and observe the behavior of mixed monolayers containing OA and OL in ocean-relevant ratios to provide insight on how film composition impacts metal–carboxylic acid binding and thus metal cation enrichment at the air–aqueous interface.…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of ions in a subphase can also influence properties of forming floating layers. It was shown that when metal ions are added to the subphase during the formation and compression of a surfactant monolayer, the carboxyl group of surfactant molecule interacts with metal ion in the subphase andforms a salt [4]. In this case, the -A isotherm shifts Жидкие кристаллы и их практическое использование.…”
Section: Introductionmentioning
confidence: 99%